2014
DOI: 10.1117/12.2055515
|View full text |Cite
|
Sign up to set email alerts
|

Lessons we learned designing and building the Chandra telescope

Abstract: 2014 marks the crystal (15 th ) anniversary of the launch of the Chandra X-ray Observatory, which began its existence as the Advanced X-ray Astrophysics Facility (AXAF). This paper offers some of the major lessons learned by some of the key members of the Chandra Telescope team. We offer some of the lessons gleaned from our experiences developing, designing, building and testing the telescope and its subsystems, with 15 years of hindsight. Among the topics to be discussed are the early developmental tests, kno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 3 publications
0
9
0
Order By: Relevance
“…There are two other papers in this conference [5,6] that discuss in some detail the lessons learned in the process of building and operating this Great Observatory. The entire process has taken thirty-eight years (and counting) from the initial unsolicited proposal of Giacconi and Tananbaum in 1976 to the upcoming celebration of the 15-th anniversary of the launch in July 2014.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…There are two other papers in this conference [5,6] that discuss in some detail the lessons learned in the process of building and operating this Great Observatory. The entire process has taken thirty-eight years (and counting) from the initial unsolicited proposal of Giacconi and Tananbaum in 1976 to the upcoming celebration of the 15-th anniversary of the launch in July 2014.…”
Section: Lessons Learnedmentioning
confidence: 99%
“…The spacecraft and mission design leverage existing heritage and benefit from simplicity of operation. Chandra, for example, has produced many Lessons Learned 12 that Lynx will incorporate. The spacecraft design and mission operations borrow heavily from the Chandra Observatory, the only X-ray observatory to date to achieve sub-arcsecond angular resolution 13 .…”
Section: Designing An Observatorymentioning
confidence: 99%
“…We anticipate benefit from the early development of high-fidelity simulations as a tool to illuminate the tall poles in the error budget, guide the choices toward performance optimization, and enable strategic comparisons by providing an integrated end-to-end measure of the entire process. 25,26 Our Chandra experience has shown that multiple independent performance predictions are needed to inject sufficient discourse into the development process to have confidence that test results will satisfy requirements, 27,28,29 so we approach the problem by starting to develop a flexible set of tools, which are specific to the mounting and alignment problem and independent of other likely methods.…”
Section: System Level Approachmentioning
confidence: 99%